Vascular ring, an uncommon presentation of BRUE in newborns - Dhruw, Sneha Singh; Saini, Abhishek; Singh, Sourabh (International Journal of Contemporary Pediatrics, 2018)
Vascular rings are a group of anomalies caused by abnormal embryologic development of the branchial arch system. They can lead to variable degrees of respiratory problems or feeding difficulties by forming a complete or partial ring compressing the trachea, the bronchi, and the oesophagus. Vascular rings not being so common, a missed diagnosis is much more common. Hence a high degree of suspicion along with appropriate imaging study is required to make a diagnosis. This case report describes an uncommon acute presentation of a vascular ring in newborn as a brief resolved unexplained event (BRUE).